2013
DOI: 10.4103/0975-7406.114309
|View full text |Cite
|
Sign up to set email alerts
|

Rare form of cherubism: Case report with review of literature

Abstract: Cherubism was first described by Jones in 1933 as “familial multilocular cystic disease of jaws.” Renamed as cherubism in 1938 because of classical characteristics of full round cheeks and upward cast of the eyes to the angelic look of the cherubs immortalized by renaissance art. It is characterized by progressive painless bilateral swelling of jaws involving either maxilla or mandible producing chubby face. It is uncommon fibro-osseous disorder of bone. Mutation in the gene encoding SH3-binding protein 2 (SH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“… 2 , 3 Some studies have reported cherubism to be a family pathology; however, both hereditary and nonhereditary cases have been described. 4 , 5 In this patient, there was no history of the disease in any of the family members, and therefore, it was a nonfamilial case. In most patients, cherubism is because of dominant mutations in the SH3BP2 gene on chromosome 4p16.3.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“… 2 , 3 Some studies have reported cherubism to be a family pathology; however, both hereditary and nonhereditary cases have been described. 4 , 5 In this patient, there was no history of the disease in any of the family members, and therefore, it was a nonfamilial case. In most patients, cherubism is because of dominant mutations in the SH3BP2 gene on chromosome 4p16.3.…”
Section: Discussionmentioning
confidence: 87%
“…Cherubism is characterized by bilateral and symmetric fibro-osseous lesions limited to the mandible, maxilla, or both. 5 , 6 Jones described that patients appeared to be “looking towards heaven” like a cherub angel, because of the round appearance of the cheeks, resulting from jaw hypertrophy. Affected children usually present with painless progressive swelling of the cheeks, frequently associated with dental malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonaggressive lesions are seen in teenagers while the aggressive form manifests in young children with rapid growth of the lesions. 1 Clinical features include painless, bilateral enlargement of the mandible and/or maxilla resulting in a rounded face along with a heavenward gaze. 5 The mandible is affected more than the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…It was renamed cherubism, as the patients look like cherubs portrayed throughout Renaissance art. 1,2 Though classified as a familial, autosomal dominant disease, sporadic cases have been reported in literature. 3 Cherubism usually manifests at around 2 years of age, grows rapidly until puberty, and regresses by around 30 years of age.…”
Section: Introductionmentioning
confidence: 99%